2019
DOI: 10.1177/0003489418820348
|View full text |Cite
|
Sign up to set email alerts
|

The Online Support Group as a Community: A Thematic Content Analysis of an Online Support Group for Idiopathic Subglottic Stenosis

Abstract: Objective: Idiopathic subglottic stenosis (iSGS) is a rare disease with few local resources for individuals to use. With the explosive growth of online social networking, platforms such as Facebook possess compelling potential to facilitate user-driven sharing of health information and peer support. This study was performed to better understand the content shared in a busy online community for individuals with iSGS. Methods: The largest online community (OC) for individuals with iSGS, Living With Idiopathic Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…It is possible that certain knowledge, skills, or attributes may be key to effective group leadership (Pomery et al, 2016 ) and could be an area of future study to inform selection and training of facilitators. Further, while past research evaluated the effectiveness of support group interventions based on severity of illness symptoms or rarity of conditions, results also suggest mental health symptoms can be reduced when utilizing support group versus wait list controls (Griffiths et al, 2012 ; Haik et al, 2019 ; Huber et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that certain knowledge, skills, or attributes may be key to effective group leadership (Pomery et al, 2016 ) and could be an area of future study to inform selection and training of facilitators. Further, while past research evaluated the effectiveness of support group interventions based on severity of illness symptoms or rarity of conditions, results also suggest mental health symptoms can be reduced when utilizing support group versus wait list controls (Griffiths et al, 2012 ; Haik et al, 2019 ; Huber et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous observational study by our group, the posts of a large Facebook group dedicated to iSGS were thematically analyzed to gain insight into the type of information exchanged. 11 The current study furthers this inquiry to more fully understand how that information influences medical decision-making by coupling data from the prospectively collected NoAAC iSGS 1000 cohort with patient information pertaining to OSC utilization. The aim of this study is to assess iSGS patient motivation for OSC membership, patient factors impacting the frequency of OSCs use, and the influence of OSC engagement on medical decision-making.…”
Section: Introductionmentioning
confidence: 98%
“…Previous work suggested that OSCs might primarily generate value through sharing of emotional experiences rather than medical information. 4 Content analysis has been undertaken to better understand what experiences individuals are sharing, 5,6 but large gaps in knowledge still remain. The only two reports investigating OSCs influence on medical decision-making are in the fields of breast and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, however, the two SGS patients included in that study were more likely to accept serial treatment than non‐SGS patients. This is also reflected in a study of an online SGS community, which showed that maximizing time between procedures, rather than having only one procedure, was prioritized 20 . Whereas recurrence rates are low with single procedures such as cricotracheal resection, many patients prefer the more favorable safety profile of endoscopic and in‐office treatments given concerns about the higher risk of complications and permanent voice changes associated with open reconstructive procedures 21 …”
Section: Discussionmentioning
confidence: 99%